(Thyroid) Hormonal regulation of breast cancer cells - Hercbergs, Aleck; Lin, Hung-Yun; Mousa, Shaker A.; Davis, Paul J. (Frontiers in Endocrinology, 2023)
Thyroid hormone as L-thyroxine (T4) acts nongenomically in physiological concentrations at its cancer cell surface receptor on integrin alphavbeta3 ('thyrointegrin') to cause cell proliferation. In the case of estrogen receptor (ERalpha)-positive breast cancer cells, T4 via the integrin promotes ERalpha-dependent cancer growth in the absence of estrogen. Thus, tumor growth in the post-menopausal patient with ERalpha-positive cancer may again be ER-dependent because of T4. Additional mechanisms by which T4 may contribute uniquely to aggressive breast cancer behavior--independently of ER--are stimulation of immune checkpoint inhibitor gene expression and of several anti-apoptosis mechanisms. These observations may call for consideration of elimination of host T4 production in breast cancer patients whose responses to standard chemotherapy are suboptimal. Euthyroidism in such a setting may be maintained with exogenous 3,3',5-triiodo-L-thyronine (T3).